Exploring the Influence of Ethical Leadership on Voice Behavior: How Leader-Member Exchange, Psychological Safety and Psychological Empowerment Influence Employees’ Willingness to Speak Out - Hu, Yixin; Zhu, Liping; Zhou, Mengmeng; Li, Jie; Maguire, Phil; Sun, Haichao; Wang, Dawei (Frontiers in Psychology, 2018)
The study of voice behavior examines the inclination of staff and team members to speak up and contribute ideas to the team. In this article, we investigate how factors such as leader-member exchange (LMX), psychological safety and psychological empowerment influence such behavior. Our findings, which are based on a sample of 308 employees working for a state-owned telecommunications company on the Chinese mainland, indicate that ethical leadership promotes employees’ voice behavior through enhanced leader-member exchange, which also leads to greater feelings of psychological safety and psychological empowerment. The theoretical and practical implications of these results are discussed.